Fulfilment of Information Needs on Families in Intensive Care Unit - Zahara Farhan; Sulastini; Devi Ratnasari; Ary Aprian (PT FORMOSA CENDEKIA GLOBAL, 2023)
The presence of family members being treated in the intensive care unit can trigger worry and anxiety for the family so that information about the patient's condition related to care and treatment is a very important aspect for the family. The purpose of this study is to find out the description of fulfilling the information needs of families in the intensive care unit. The research design is quantitative descriptive, the sample of this study is family members who are responsible for the patient, totaling 35 respondents, the sampling technique uses purposive sampling, the research instrument uses the Critical Care Need Family Inventory (CCFNI), data analysis uses mean score. The results showed that almost all of the aspects of fulfilling the information needs about the patient's condition in the family 80% were fulfilled, the aspects of fulfilling the information needs about the action of treatment and the duration of treatment for majority 74.5% were fulfilled, and the aspects of fulfilling the information needs about the length of care and treatment 51.4% were fulfilled. The performance of doctors, nurses and other health workers is an important role for families in intensive care unit